Advances in the medical management of bowel endometriosis. (March 2021) - Vercellini, Paolo; Sergenti, Greta; Buggio, Laura; Frattaruolo, Maria Pina; Dridi, Dhouha; Berlanda, Nicola
Abstract: Endometriosis infiltrating the bowel can be treated medically in accurately selected women not seeking conception and without overt obstructive symptomatology. When the rectosigmoid junction is involved, the probabilities of intestinal symptoms relief, undergoing surgery after treatment failure, and developing bowel obstruction during hormonal treatment are around 70%, 10%, and 1–2%, respectively. When the lesion infiltrates exclusively the mid-rectum, thus in cases of true rectovaginal endometriosis, the probabilities of intestinal symptoms relief and undergoing surgery are about 80% and 3%, respectively. Endometriotic obstructions of the rectal ampulla have not been reported. A rectosigmoidoscopy or colonoscopy should be performed systematically before starting medical therapies, also to rule out malignant tumours arising from the intestinal mucosa. Progestogens are safe, generally effective, well-tolerated, inexpensive, and should be considered as first-line medications for bowel endometriosis. Independently of symptom relief, intestinal lesions should be checked periodically to exclude nodule progression during hormonal treatment. Highlights: Bowel endometriosis can be treated medically in accurately selected women without overt obstructive symptomatology. Hormonal drugs might control, but not cure bowel endometriosis, and this may imply the use of medications for years. Progestogens are safe, effective, generally well-tolerated, inexpensive, and should be considered as first-line medications. Most of the patients with rectosigmoid and rectovaginal endometriosis can be managed successfully with hormonal drugs. The risk of obstruction during therapy is 1–2% with rectosigmoid endometriosis, and negligible with rectovaginal disease.